The Impact of ICT on Fleet Maintainance and Disposal in an Organisation - Joan Maclyne Linda Adyero (Uganda Christian University, 2023)
The studywascarried out at Aponye Company Uganda Limited. The study aimed at examining the impact ICT on fleet maintenance and disposal in an organization.The objectives of the study included; to examine the types of technology Aponye Company Limited can embrace to maintain their fleet better,. to examine the key factors needed to embrace ICT for fleet maintenance and disposal in Aponye Company Limited, to examine the benefits of adopting ICT in fleet maintenance and disposal in Aponye Company Limited. The researcher u majorly used a case study alongside qualitative and quantitative research methods to study the topic on ground. The researcher used both primary and secondary data sources ,tools like questionnaires. To sum up the study, the researcher concluded that the impact of ICT on day to day running of Aponye company was noticed amongst the respondents as it can be seen that a decent number of the respondents being aware of at least three types of fleet technology which shows the willingness to embrace ICT,additionally, the researcher noted that the respondents were strongly versed with the factors that lead to the adoption of ICT thus a very good sign that they are well aware of the drivers to adapt ICT this assures the respondent that the administration know what to do in order to implement increased usage of ICT and lastly the benefits were the most positively responded to as most respondents were well versed with thus meaning they can easily adapt to ICT due to their awareness of what they are set to achieve should they adapt ICT. The researcher came up with recommendations such as investing more in intensive research, continuous training of staff, and employment of highly skilled staff as well as improving their change management.
This is a dissertation.